(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Adolescence represents a critical period marked by significant changes in social interactions and self-perception. During this developmental phase, adolescents form essential aspects of their self-image and social competence, crucial for their overall well-being and future success. This study explores how adolescents’ perceptions of their parents’ parenting styles influence their social competence and self-image. Specifically, it investigates the impact of different perceived parenting approaches on these developmental outcomes among adolescents in Kerala, a region experiencing cultural shifts and socio-cultural challenges. Using a correlational research design, data was collected from 593 adolescent students attending high school and higher secondary school in Kerala. Measures included the Perceived Parenting Scale, Social Competence Scale, and Index of Self-Image Scale. Results indicate significant correlations between perceived parenting styles and adolescent social competence and self-image. Parenting dimensions such as acceptance, indulgence, realism, moralism, and discipline consistently showed positive associations with these outcomes. Notably, parental acceptance and indulgence, along with discipline and realistic role expectations, were found to play interconnected roles in shaping adolescent development.